Non-alcoholic Wernicke's encephalopathy: broadening the clinicoradiological spectrum - Santos Andrade, C (The British Institute of Radiology., 2010)
Wernicke's encephalopathy (WE) is a serious neurological disorder secondary to thiamine deficiency. Improved recognition by radiologists and allied health providers of the different clinical settings and imaging findings associated with this emergency can optimise the management of this condition and help prevent its severe consequences. The aim of this study is to illustrate the broad clinicoradiological spectrum of non-alcoholic WE, while emphasising atypical MRI findings.